Characteristics of the Moho as revealed from explosion seismic reflections beneath the Mizuho Plateau, East Antarctica - Yamashita, Mikiya; Kanao, Masaki; Tsutsui, Tomoki (National Institute of Polar Research, 2002)
P(論文) Seismic exploration was conducted on the Mizuho Plateau, East Antarctica, during the 1999-2000 austral summer season by the 41st Japanese Antarctic Research Expedition (JARE-41) Seismic shot records were obtained with clear arrivals of the later reflected phases by a total amount of 3300 kg dynamite charges in seven explosions along the Mizuho traverse route 180 km in length The purpose of this study is to investigate characteristics of the Moho discontinuity from reflective evidence by using explosive seismic waves First, we used the mirror image method for the travel time data of Moho reflected waves (PmP phases) Optimal image points were determined to minimize root-mean-square residuals between the observed and the calculated travel times by an iterative grid search at 1 km intervals The depth of the reflected Moho and the averaged incident angles were determined by taking the P wave velocity of the crust as a parameter The obtained Moho depth and the associated dipping angle were well correlated with those from the previous reflection study Amplitude spectrum analysis was also applied to obtain the difference in peak frequency of the spectrum between the PmP phases and the direct P phases The observed spectral ratios of the reflected PmP phases to the direct P phases indicate spectral peaks at 9 5 and 19 0 Hz, and a spectral trough at 13 8 Hz, respectively This pair of spectral peaks and the trough can be explained by the existence of a thin reflecting layer of 690-860 m thickness just beneath the Moho discontinuity The thin layer may have relatively lower velocities of 7 0-7 8 km/s than those of the surrounding uppermost mantle These relatively low velocity layers around the Moho are considered to be composed of clino-pyroxenite and/or pyroxenehornblende gneiss by comparison with high-pressure laboratory measurements of metamorphic rocks from the Liitzow-Holm Complex departmental bulletin paper